Optimized FOI-TD controller for automatic generation control of restructured power systems with sodium-ion batteries - Nanthini B S; Ilanji Akilandam Chidambaram; Rajeswaran Sivasangari (Bulletin of Electrical Engineering and Informatics, 2026)
This article examines a novel control technique known as the fractional order integral-tilt derivative (FOI-TD) controller, which was used for automatic generation control (AGC) with a two-area restructured power system. The FOI-TD controller enhances performance by integrating tilt- derivative control with fractional-order control. Fractional-order control offers greater flexibility and allows for more precise tuning of the controller's response. The tilt component modifying the proportional term minimizes overshoot and improves settling times. The control parameters of the FOI-TD controller are optimized using the moth flame optimization (MFO) method and the efficacy of the given algorithm is associated with recent studies using meta-heuristic techniques. Analysis indicates that the MFO-optimized FOI-TD controller substantially enhances the dynamic response of the AGC loop and compared with traditional controllers. This enhancement includes reduced peak deviations, shorter settling times, and better suppression of area frequencies and tie-line power oscillations across different transaction scenarios within restructured power system. To further enhance AGC performance, fast-acting energy storage systems, like sodium- ion batteries (SIB), are integrated into the control area. The coordinated operation of the SIB units improves system dynamics and stability by mitigating initial frequency drops and tie-line power variations caused by sudden load disturbances.